Impact of Curing Periods on the Evaluation of Thermal, Mechanical Properties, and Energy Consumption of Concrete Buildings - Abdallah Talhaoui; Naima Fezzioui; Adel Benidir (The Journal of Engineering and Exact Sciences)
This study examines the impact of the curing period on the thermal and mechanical properties of concrete and its subsequent effect on building energy consumption. The research methodology is divided into two parts: experimental and simulation. In the experimental section, concrete specimens were created using regular concrete with a dosage of cement of 350 Kg/m³, and curing periods were varied (without curing, 3, 7, 14, 21, and 28 days) to assess thermal conductivity, density, ultrasonic pulse velocity, and compressive strength at 28 days. The results indicated that compressive strength increased by 71% between uncured and 28-day cured specimens, ultrasound propagation speed increased by 15%, and thermal conductivity increased by 31% with longer curing periods. A simulation using TRNSYS software estimated the energy consumption of a reference building with varying concrete properties based on the curing period. The simulated building consisted of three rooms, a hall, and a kitchen, with double exterior walls of 25 cm thickness and interior walls of 10 cm thickness. The findings revealed that longer curing periods contributed to increased energy consumption in the building. This study provides valuable insights into the relationship between curing periods, concrete properties, and their effect on the energy efficiency of concrete buildings.